FRACTAL ANALYSIS OF THE HUMAN CEREBELLUM WHITE MATTER - Степаненко О. Ю.; Maryenko, N.I. (World of Medicine and Biology, 2017)
The aim of the study – to investigate the fractal dimension of the white matter of the human cerebellum. Material and methods. The study involved 100 human cerebella of people of both sexes, who died from causes not related to brain pathology, aged 20-95 years. Serial sections of the vermis and hemispheres were performed in the central sagittal and parasagittal planes with a step-by-step interval of 5 mm (from 0 to 40 mm). Fractal analysis of digital images was carried out by the box-counting method. The statistical distribution of the values of the fractal dimension was estimated using methods of the variational statistics. Results. Fractal index (FI) is an indicator of the degree of filling the space with a fractal structure. The values of the white matter of the cerebellum are distributed in a relatively small range of values: from 1.20 to 1.50, the mean value is (1.372 ± 0.006). The fractal index variability is very low, as are the apparent morphological differences in objects with different values of the fractal index. The values of the fractal index of the white matter of the cerebellum are normally distributed. The difference in the values of the white matter of the vermis and hemispheres, the parasagittal sections of the hemispheres located at different distances from the median sagittal plane, and also the symmetrical sections of the right and left hemispheres is insignificant and is not statistically reliable. The values of the fractal white matter index of the vermis and hemispheres are related to each other by a strong correlation relationship (r = 0.804 ÷ 0.953; P